NF-κB Signaling in the Brain of Autistic Subjects. (20th October 2011) - Malik, Mazhar; Tauqeer, Zujaja; Sheikh, Ashfaq M.; Wen, Guang; Nagori, Amenah; Yang, Kun; Brown, W. Ted; Li, Xiaohong
Abstract : Autism is a neurodevelopmental disorder characterized by problems in communication, social skills, and repetitive behavior. Recent studies suggest that apoptotic and inflammatory mechanisms may contribute to the pathogenesis of this disorder. Nuclear factor-κ B (NF-κ B) is an important gene transcriptional factor involved in the mediation of inflammation and apoptosis. This study examined the activities of the NF-κ B signaling pathway in the brain of autistic subjects and their age-matched controls. The NF-κ B activation is also determined in the brain of BTBR mice, which is a promising animal model for study of pathogenic mechanisms responsible for autism. Our results showed that the level of IKKα kinase, which phosphorylates the inhibitory subunit Iκ Bα, is significantly increased in the cerebellum of autistic subjects. However, the expression and phosphorylation of Iκ Bα are not altered. In addition, our results demonstrated that the expression of NF-κ B (p65), and the phosphorylation/activation of NF-κ B (p65) at Ser536 are not significantly changed in the cerebellum and cortex of both autistic subjects and BTBR mice. Our findings suggest that the NF-κ B signaling pathway is not disregulated in the brain of autistic subjects and thus may not be significantly involved in the processes of abnormal inflammatory responses suggested in autistic brain.